Hypertonic saline for treatment of shock: have we looked for everything? - Silva,Mauricio Rocha e (2014)
This review is dedicated to the memory of Luis Poli de Figueiredo, who is responsible for much of what we know about small volume resuscitation. Small volume hypertonic resuscitation was originally based on the concept that a physiologically significant blood volume expansion follows the administration of a comparatively small volume of hypertonic fluid. Because hypertonicity is a physiological vasodilator, its use after severe blood loss induces reperfusion. Previously reported research disclosed a number of additional properties of hypertonic NaCl, amongst them (i) the correction of endothelial and red cell edema with significant consequences in terms of capillary blood flow; (ii) modulation of the immune system, with applications repercussions in the field of sepsis. This review covers developments in this field that occurred from 2005 through 2013. We discuss the discrepancy between animal experiments and human trials, and argue that the basic objective of most multicenter clinical trials may have been based upon a poor strategy.